Association between tobacco and alcohol consumption in women aged 15 to 49 in Costa Rica, according to the results of the Survey of Women, Children and Adolescents, 2018 - Gómez González, Daniela; Fantin, Romain; Valverde Manzanares, Cindy; Gamboa Gamboa, Tatiana; Arias Jiménez, Stephanie; Carrillo Barrantes, Jorge Daniel (Población y Salud en Mesoamérica, 2022)
This article analyses the association between consumption of tobacco and alcohol among Costa Rican women ages 15 to 49. A National Women, Children, and Adolescents Survey was disseminated across Costa Rica in 2018 (n = 7,487). The percentages of women who consumed tobacco and alcoholic beverages were calculated by age, socio-economic indicators, and civil status. A logistic regression design was used to analyze the relationship between tobacco and alcoholic beverages consumption. The relationship between tobacco and alcohol consumption was confirmed. Women who consumed alcohol four times or more in the past month had a higher prevalence of tobacco use (OR = 18.80 [11.25-31.41]). On the other hand, women who smoke had a lower prevalence of alcohol consumption (OR = 4.09 [2.67-6.26]) than women who smoke occasionally (OR = 8.86 [4.83-16.24]). There is an association between tobacco consumption and alcohol consumption in women between 15 and 49 years old. This relationship is present with greater force in young, single women and residents of urban areas.